New variants of soybean cultivation under the current climate changes - Felicia Cheţan; Cornel Cheṭan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The yield dates recorded in the period 2016-2018 indicate that soybean is less demanding at the soil cultivation system, so that in the three years of experimentation, the average yield achieved in the classical soil cultivation system had a close value of that obtained in the minimum system (chisel and disk), the differences being between 29-245 kg/ha. By marketing the production, it obtains the highest profit in the minimum soil cultivation system - the chisel variant of 1174 lei/ha followed by the classical system with 967 lei/ha and the disk variant 829 lei/ha. During these three experimental years there were very rapid changes in the weather, at hot to cold and vice versa, the torrential rains abundance of followed by long droughts. Higher values of available water reserve in the soil (Ra m3/ha) were determined in the classical system in the rainy years, but at the same time there is a faster loss than the minimum system where the accumulation of water in the soil is made more difficult but it's slower.
Keywords: Q01; Q15; Q16; 330; tillage system; clime; water reserve; yield; soybean